Temperature-dependent population growth of three species of stored product mites (Acari: Acaridida) - Aspaly, Gamila; Stejskal, Václav; Pekár, Stano; Hubert, Jan (Experimental & applied acarology, 2007)
The pest potential of stored product mites depends on the reproduction rate that is affected by the environmental conditions. In this study we investigated the effect of temperature, ranging from 5 to 35 degrees C, on the population growth of three important mite species, Acarus siro, Tyrophagus putrescentiae and Auleroglyphus ovatus at 85% r.h. Starting with 10 individuals the population increase of mites was observed after 3 weeks of cultivation, or after 6 weeks for those kept at low temperatures (5, 10, 12.5, and 15 degrees C). The rate of increase was calculated for each temperature and species. The obtained data were fitted with polynomial models. The mite population growth rates increased with increasing moderate temperatures until 25 degrees C, when r ( m )-values were 0.179, 0.177 and 0.190 for A. siro, A. ovatus and T. putrescentiae, respectively. The lower development threshold was 10.2 degrees C in all three species. Estimated upper temperature threshold was higher in T. putrescentiae (49 degrees C) than in A. siro and A. ovatus (38 degrees C). Simulation of the rate of population increase under ideal conditions, using real temperature records obtained from Czech grain stores, showed that the pest mite populations increase only during 3.5 months within a typical 9-month storage season in Central Europe. These results indicate that control of mites, be it chemical, physical or biological, is recommended during the months when allergens and pests are produced, i.e. from September to mid November and in May.
Keywords: populační růst; Population Growth; Edible Grain; Food Parasitology; jedlá semena; teplota; roční období; Acaridae; Animals; Česká republika; Temperature; potravinářská parazitologie; Seasons; zvířata; Czech Republic